Pertanian Ramah Lingkungan Melalui Pelatihan Pembuatan Pupuk Organik Cair Dari Limbah Dapur - Bahtiar, Yuyun (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Training on making liquid organic fertilizer from kitchen waste was introduced as an effort to encourage sustainable agriculture at the community level. This study aims to evaluate the impact of training in making liquid organic fertilizer from kitchen waste on agricultural practices in Sidomulyo village. The research methods used include surveys, interviews with farmers, and analysis of agricultural yield data before and after the implementation of liquid organic fertilizer. The research results show that this training has succeeded in increasing the understanding and application of sustainable agricultural practices among farmers. The positive impact of this training includes increasing plant productivity. Training also provides economic benefits by reducing fertilizer costs and increasing farmer income through better crop yields. Implementation of training on making liquid organic fertilizer from kitchen waste in Sidomulyo village is a concrete step in encouraging sustainable and environmentally friendly agriculture. The results of this research have important implications for similar regions that want to introduce sustainable agricultural practices by utilizing local resources.